Quo Vadis English Language Learning System in Pesantren? - Umar, Umar; Yuliasri , Issy; Rukmini , Dwi; Rozi, Fahrur (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The integration of English language education into pesantren presents a growing pedagogical challenge in Indonesia, where traditional religious instruction often dominates curriculum design and classroom culture. Despite increasing awareness of English as a global communication tool, its implementation in pesantren remains fragmented and culturally misaligned. This study addresses a critical gap in understanding how pesantren leadership, educational substance, and institutional culture influence English instruction. Focusing on Darussalam Buntet pesantren—a semi-modern pesantren that integrates kitab kuning with formal education—this research uses a qualitative descriptive method grounded in Lawrence Friedman’s legal system theory, encompassing structure, substance, and culture. Data were gathered through interviews and observations. Findings reveal that the structure of pesantren is fully governed by the kiai, who morally supports English instruction but has not issued binding policies to institutionalize it. Substantively, the pesantren shows openness to modern knowledge, yet English remains peripheral in its vision and curriculum. Culturally, the use of English in students' daily interactions is minimal, limited primarily to extracurricular programs such as English Day and English Club. In response, this study proposes a hybrid pedagogical model that combines Communicative Language Teaching (CLT) with Content-Based Instruction (CBI), incorporating Islamic themes—such as thaharah and prayer—to make English both linguistically effective and religiously relevant. This approach aligns with pesantren values and students’ cognitive frameworks, thereby enhancing motivation and legitimacy. The study recommends integrated curriculum reform, strengthened teacher capacity, and leader-driven policies that respect pesantren traditions while preparing students for global engagement through English proficiency.